Centralized Hybrid Equalization for Cell Free mMIMO mmWave based Systems - Kassam, J.; Castanheira, D.; Silva, A.; Dinis, R.; Gameiro, A. (2022 13th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2022)
Cell-free massive multiple input multiple output (CFmMIMO) is one of the promising technologies for beyond 5G/6G wireless communications due to its advantages in overcoming the inter-cell interferences constraints in ultra-dense networks. In this paper, we propose a low complexity analog precoder with a centralized hybrid analog-digital multi-user equalizer for millimeter-wave (mmWave) CF mMIMO systems. In the transmitter, a low complexity analog precoder is applied based on the partial channel state information (CSI) knowledge, i.e., only the average angle of departure (AoD) information. While in the centralized hybrid receiver, the central unit (CU) handles all processing that requires access to the global CSI. Herein, the analog coefficients of the equalizer are obtained by minimizing the mean square error (MSE) between the transmit and receive signals using the weighted Frobenius norm as a metric, whereas an optimum linear MSE equalizer is used to get the digital part. We also compare the considered CF scenario with the small cells (SCs) based one for different hybrid schemes. The results show that the proposed precoder combined with the hybrid equalizer can achieve very close results to a fully digital counterpart. Moreover, the performance of the considered CF scenario is better than the SCs based one for all hybrid schemes.